The significance of institutional culture in enhancing the validity of international criminal tribunals - Mistry, Hemi (Brill, 2017)
When considering the validity of international criminal tribunals, focus is typically and appropriately upon areas of substantive law and procedure and questions of prosecutorial policy. However, to the extent that it is within the capacity of judges to address and resolve challenges to the validity of the institution, in order for judges to formulate and implement effective solutions to those challenges it is imperative that an institutional culture is cultivated that is conducive to those ends. This paper explains the relationship between judicial culture and institutional legitimacy, and highlights how recent jurisprudence of the International Criminal Court (ICC) suggests that there is a need for the adoption and implementation of measures to promote the development of a robust institutional culture conducive to resolving the challenges faced by the ICC.